Kajian Manuskrip Al-Tasrif Karya Al-Zahrawi - Sopan Setiawan; Nyimas Umi Kalsum (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2026)
Philological studies are a branch of scholarship that examines ancient manuscripts as sources of historical, cultural, linguistic, and scientific information. One of the most significant manuscripts in the history of Islamic civilization is Al-Tasrif liman ‘Ajiza ‘an al-Ta’lif by Abu al-Qasim Al-Zahrawi. This manuscript is recognized as an influential encyclopedia of Islamic medicine that greatly contributed to the development of medical science in both the Eastern and Western worlds. This article discusses the identification of the manuscript as well as the main contents of Al-Tasrif. The study reveals that the manuscript possesses high scientific, historical, and philological value because it contains comprehensive discussions on surgery, medical instruments, pharmacy, and medical ethics. Furthermore, the manuscript reflects the intellectual advancement of Islamic civilization during the medieval period.